Nature And Reasons For The Origin Of Problem Loans (Global Scientific Review, 2025)
The article is devoted to the analysis of methods of managing problem loans in commercial banks. It systematizes the key factors that contribute to the formation of problem debt. The theoretical aspects of managing problem assets are considered. Also, measures are proposed aimed at reducing the share of problem loans in Uzbek commercial banks, based on the experience of European countries